Potential Antibiotic-Drug Interactions in Hospitalized Patients : A Retrospective Cross Sectional Study - Syilvi Rinda Sari; Kiki Rawitri; Hindri Syahputri; Muhammad Amin Nasution; Nia Novranda Pertiwi (LPPM Universitas Abdurrab, 2025)
Infectious diseases are frequently seen in hospitalized patients, and antibiotics are among the most commonly prescribed drugs. Patients in the hospital frequently experience drug interactions because their severe conditions frequently necessitate the simultaneous administration of many medications. This study aims to determine the frequency of potential drug interactions between antibiotics and other drugs in hospitalized patients at Dr. Pirngadi Hospital, Medan, Indonesia. This study uses an observational method with a retrospective cross-sectional study design on 300 patients who met the inclusion criteria in January-December 2023. Potential antibiotic drug interactions seen from the Medscape application. The results showed that only 20.33% of the total sample experienced potential interactions between antibiotics and other drugs in patients at Dr. Pirngadi Hospital in the period January-December 2023, namely only 61 patients from a total sample of 300 patients with 84 cases of potential interactions between antibiotics and other drugs. The potential drug interactions that occur are pharmaceutically as much as 5.26%, pharmacokinetically as much as 10.53%, and the majority, pharmacodynamically, as much as 84.21%.